HBR's 10 must reads on leadership. (Boston, Massachusetts : Harvard Business Review Press, 2011)
"Go from being a good manager to being an extraordinary leader. If you read nothing else on leadership, read these 10 articles. We've combed through hundreds of Harvard Business Review articles on leadership and selected the most important ones to help you maximize your own and your organization's performance. This book will inspire you to: motivate others to excel; build your team's self-confidence; provoke positive change; set direction; encourage smart risk-taking; manage with tough empathy; credit others for your success; increase self-awareness; draw strength from adversity"--Page 4 of cover.
What makes a leader? / Daniel Goleman -- What makes an effective executive / Peter F. Drucker -- What leaders really do / John P. Kotter -- The work of leadership / Ronald A. Heifetz and Donald L. Laurie -- Why should anyone be led by you? / Robert Goffee and Gareth Jones -- Crucibles of leadership / Warren G. Bennis and Robert J. Thomas -- Level 5 leadership: the triumph of humility and fierce resolve / Jim Collins -- Seven transformations of leadership / David Rooke and William R. Torbert -- Discovering your authentic leadership / Bill George, Peter Sims, Andrew N. McLean, and Diana Mayer -- In praise of the incomplete leader / Deborah Ancona, Thomas W. Malone, Wanda J. Orlikowski, and Peter M. Senge.
Includes index.
Description based on online resource; title from electronic title page (ProQuest Ebook Central, viewed February 11, 2019).
WorldCat record variable field(s) change: 050
Keywords: Leadership; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Leadership; elektronické knihy; electronic books